A More Robust Gut Microbiota in Calorie-Restricted Mice Is Associated with Attenuated Intestinal Injury Caused by the Chemotherapy Drug Cyclophosphamide - Tao Liu (American Society for Microbiology, 2019)
ABSTRACT Cyclophosphamide (CTX) is widely used in cancer chemotherapy, but it often induces mucositis, in which the disruption of the gut microbiota might play a pivotal role. Whether the manipulation of the gut microbiota can be used as a strategy to improve CTX-induced mucositis remains to be studied. Here we observed the effects of a 4-week calorie restriction (CR) on CTX-induced mucositis. Compared with ad libitum-fed mice, CR mice showed significantly less mucositis in response to CTX, including lower intestinal permeability, less bacterial translocation, higher number of epithelial stem cells, and less epithelium damage. CTX induced significant shifts of the gut microbiota of the gut microbiota in ad libitum-fed control mice. In contrast, CR mice showed no significant change in their gut microbiota in responding to CTX treatment. CR significantly enriched the gut microbiota in Lactobacillus and Lachnospiraceae which are known to mitigate inflammation and improve gut barrier function. These findings suggest that CR remodeled gut microbiota is more robust and may contribute to attenuate the side effects of cyclophosphamide, which supports the concept that cancer chemotherapy would benefit from strategies targeting the gut microbiota. IMPORTANCE Improving the gut microbiota via calorie restriction is beneficial for human health. Our findings showed differential responses between calorie-restricted mice and ad libitum-fed mice. Compared with the ad libitum-fed mice, the calorie-restricted mice were less susceptible to cyclophosphamide side effects otherwise observed on the gut integrity and its microbiota. These results show the potential benefits of manipulating the gut microbiota with CR prior to cancer chemotherapy.